2008
DOI: 10.2166/wst.2008.555
|View full text |Cite
|
Sign up to set email alerts
|

Use of RNA-based genotypic approaches for quantification of viable but non-culturable Salmonella sp. in biosolids

Abstract: Recent research efforts demonstrated an increase in fecal coliform counts in anaerobically digested biosolids after dewatering. Variety of bacteria enters viable but nonculturable (VNC) state as a survival response when exposed to environmental stress. Increase in coliform concentration after digestion and dewatering processes have been attributed to cells going into a viable but non-culturable state implying that traditional coliform enumeration methods are not sufficient to determine number of viable cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…RNA-based genotypic approaches targeting stress related genes have been made to identify VBNC cells of Salmonella spp. in biosolids qPCR (76). For the detection of V. cholerae in the VBNC state, 16S rRNA and mRNA for tuf, rpoS , and relA have been targeted (77).…”
Section: Detection Methodsmentioning
confidence: 99%
“…RNA-based genotypic approaches targeting stress related genes have been made to identify VBNC cells of Salmonella spp. in biosolids qPCR (76). For the detection of V. cholerae in the VBNC state, 16S rRNA and mRNA for tuf, rpoS , and relA have been targeted (77).…”
Section: Detection Methodsmentioning
confidence: 99%
“…Since the introduction of the concept or sublethally injured or viable but nonculturable (VBNC) cells by Byrd and Colwell in the 1980's [1], there is increasing evidence for the existence of such a state in microbes, particularly in the aquatic environment that elicits a myriad of interrelated sub-lethal microbial stresses such as nutrient starvation and osmotic stress [2, 3] (Table 1). This is a cause for concern because of evidence that microbial pathogens in such a state may still retain their capacity to cause infections after ingestion by fish, animals, or by humans, despite their inability to grow under conditions employed in laboratory-based procedures for determining their presence in water [4].…”
Section: Viable But Nonculturable Forms Of Waterborne Bacteriamentioning
confidence: 99%
“…RNAbased genotypic approaches targeting the detection of stress related genes in VBNC has been used in Salmonella spp. in biosolid qRT-PCR, for detecting the VBNC state of Vibrio cholera Escherichia coli, Pseudomonas putida and Legionella pneumophila (Buse et al, 2013;Dunaev et al, 2008;González-Escalona et al, 2006;Gunasekera et al, 2002;Vora et al, 2005;Yaron and Matthews, 2002). To facilitate those studies, several housekeeping genes have been identified for the opportunistic human pathogen P. aeruginosa under various experimental conditions.…”
Section: Introductionmentioning
confidence: 99%